Specimen size effect on the durability indexes determination for cement-based materials - Visairo-Méndez, Rebeca; Torres-Acosta, Andrés Antonio; Alvarado-Cárdenas, Roberto (Revista ALCONPAT, 2019)
In this project is required to determine if there is any result variation in durability indexes due to size effect in sizes of mortar specimens. Cubes 5 x 5 cm, 5 x 10 cm and 10 x 20 cm cylinders for each mortar type were considered. It was found that in certain indexes (WER, TVC, and CS) results did not depend on specimenÂ´s geometry. Nonetheless, UPV index result presented differences up to 17.5 % between the cubes and the 10 x 20 cm cylinders. Îµeff index result showed an interesting difference between the cubes and the 5 x 10 cm cylinders used in full length. Therefore, it is recommended to restrict the height of the specimen to a standard value